SAT0115 Rheumatoid Arthritis Also Disadvantages Female and Younger Patients for Cardiovascular Disease: Results of a Systematic Review with Meta-Analysis. (9th June 2015) - Fransen, J.; Kazemi-Bajestani, S.M.; Bredie, S.J.; Popa, C.D.
Abstract : Background: The increased cardiovascular (CV) risk in rheumatoid arthritis (RA) patients is not explained by traditional risk factors. In the general population CV risk is higher in males than in females, and risk increases with age. It may be that the load of RA increases the risk in female and in younger patients, but whether this risk augmentation occurs and to which extent is unclear. Objectives: To analyse whether the influence of age and gender on CV risk differs in RA patients as compared to the general population, using meta-analysis of direct comparative studies. Methods: Systematic literature searches were performed in MEDLINE, Cochrane Library and EMBASE databases (1980 to December 2013). Two reviewers independently identified observational studies that reported incidence of CV events (morbidity and mortality) in RA patients compared to the general population, stratified for gender and/or age. One reviewer extracted data on comparative statistics (incidence rate ratio (IRR) or standardized mortality rate, standardized morbidity rate), stratified for age, gender and nature of event (ischaemic stroke, coronary artery disease, combined CV events). Cochrane's Review Manager software 5 was used for meta-analysis. Results were combined weighted for group size in a random effects model, and were presented in forest plots. Heterogeneity was analysed using I 2 . Results: We identified 1167 unique references, 60 were reviewed full-text and 14 studies were included (8 with ischaemic stroke data, 7 with coronary artery disease data, 12 with CV data). Compared to the general population, female and male RA patients have a similar higher risk (95% CI) to develop ischaemic stroke, with an IRR of 1.35 (1.30 – 1.40) and 1.31 (1.21 – 1.43) respectively. The excess risk to develop coronary artery disease was slightly higher in RA females with an IRR of 1.65 (1.54 – 1.76) compared to RA males with an IRR of 1.55 (1.41 – 1.69). The same kind of results were seen in combined CV disease, with an IRR of 1.57 (1.49 – 1.66) for females and 1.51 (1.43 – 1.59) for males. Younger RA patients had the highest excess risk for CV disease as compared to the general population, with an IRR (95% CI) of 2.39 (1.64 – 3.48) if <50 years; 1.86 (1.63 – 2.11) if 50-65 years; and 1.27 (1.17 – 1.39) if >65 years. Differences between age groups were significant (p<0.0001) and the same relation was seen for females and males. Mortality studies were too few to analyse further. Conclusions: The excess risk on CV disease is similar for female and male RA patients and the excess risk is largest in the youngest patients. Thus, RA also disadvantages the female and younger patients for CV disease, which should guide clinical practice. Disclosure of Interest: None declared